Biological and Biogenic Crystallization - Prywer, Jolanta (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The intention of the Special Issue ""Biological and Biogenic Crystallization"" was to create an international platform aimed at covering a broad field of results involving the crystallization of biological molecules, including virus and protein crystallization, biogenic crystallization including physiological and pathological crystallization taking place in living organisms (human beings, animals, plants, bacteria, etc.), and bio-inspired crystallization. Despite many years of research on biological and biogenic crystals, there are still open questions as well as hot and timely topics. This Special Issue contains seven articles that present a cross-section of the current research activities in the of field of biological and biogenic crystals. The authors of the presented articles prove the vibrant and topical nature of this field. We hope that this Special Issue will serve as a source of inspiration for future investigations, and will be useful for scientists and researchers who work on the exploration of biological and biogenic crystals.